On the History of Studying and Publishing Kalmyk Folk Songs - B. Borlykova (Oriental Studies, 2018)
The article describes the history of study and publication of Kalmyk folk songs. It is based on the published and archival data. Domestic and foreign scholars, travelers, missionaries were engaged in collecting Kalmyk songs. Their contribution can't be overestimated as, in fact, they were the first to write down and to record Kalmyk folk songs for more than two hundred years since 1776. Currently, the Archive of the Russian Geographical Society contains ancient manuscripts of Kalmyk folk songs translated into Russian from the old Kalmyk language. For example, E. Dzhabdykov’s manuscript “Kalmyk riddles, songs and sayings of the Astrakhan province”, Sh. Sandzhirkhayev’s manuscript “Songs of Kalmyks”, “Songs and fairy tales of the Kalmyk people” manuscript. A.M.Pozdneev’s manuscript “Wedding songs of Kalmyks” is stored in the Fund for handwritten manuscripts of (IOS RAS) the Institute of Oriental Studies of the Russian Academy of Sciences. A great interest to the researchers of Kalmyk folk song are the funds of the Phonogram-Archive of the Pushkin House at the Institute of Russian Literature of the Russian Academy of Sciences (IRLI RAS) where unique materials on the Kalmyk folk music are stored. Among them one can find phonographic cylinders as well as manuscripts of music notes and texts of Kalmyk folk songs such as “The material collected by Vasily Dmitriyevich Benevsky in the Bolshederbetovsky ulus of Bashanta in 1921”, “The text of Kalmyk songs collected by the Burdukovs” and others. So, due to the excursus on the history of recording the Kalmyk song folklore and its study it became evident that both folklore records and manuscripts of music notes of the XVIII and the beginning of the XX century represent a valuable source of new problems to investigate in this field.